An exploratory examination of the influence of national culture on cross national diffusion: A case study on the MENA region - Shihanah AlMutairi; Dorothy Yen (Cogent Business & Management, 2022)
The purpose of this paper is to determine whether country-specific variables can explain differences in diffusion patterns observed across countries from the MENA region. Specifically, we examine the relationship of several indicators on innovation and imitation levels pertaining to seven Arab States and hypotheses on the direction and significance of each variable on the diffusion patterns. The study employed two prevalent theories in the literature, Hofstede's national culture theory and the Bass model, which have been used in conjunction to explain how cultural differences can affect levels of innovativeness. The present study's findings contribute to the literature by providing the characteristics of innovative countries, which are to be high UAI, low LTO, and high IVR countries and imitative countries, which are found to have low literacy rates, low urbanization, and ranked as high PDI. Originality/value: The present study was able to isolate national cultural differences in imitative behaviour, which is an objective that was understated in most cross-national diffusion literature, seeing as most emphasis is put on the innovative profiles and innovative characteristics of societies.
Keywords: 650; Arab States; Bass model; diffusion of innovations; MENA region; national culture